The Effect of Lavender Aromatherapy on Reducing Anxiety Levels in Students - Adinda Rahmawati; Annisa Nurida; Nova Primadina; Rony Subagyo (Rifa'Institute, 2022)
Introduction: Students have a lot of lecture activities; the pandemic requires all these activities to be done at home. This situation causes the stress and anxiety levels of students to increase. Lavender was chosen as one of the aromatherapy variants chosen to reduce anxiety levels. Lavender contains linalool which has anti-anxiety, relaxation, and drowsiness effects. One of the uses of lavender flower aromatherapy (Lavandula angustifolia) is inhalation to get benefits directly into the body. Method: The method used is a literature review, namely by reviewing several library sources through searching using the online databases of Google Scholar and PubMed. Objective: To determine the benefits of lavender aromatherapy on reducing anxiety levels in students. Results and Discussion: Based on the results of the study of several literature in 11 journals with student respondents, it was found that anxiety was grouped into behavioral, cognitive, and affective responses. Giving lavender aromatherapy to reduce anxiety levels can be done by inhalation, drops, evaporation, application of oxygen masks, and spray techniques. Lavender aromatherapy is effective for reducing anxiety in students. Conclusion: Lavender oil is well-known aromatherapy for its sedative, hypnotic, and antineuro depressive effects. Lavender aromatherapy can reduce anxiety levels in students.